Synthesis of Montelukast-Androsterone Derivative and its Relationship with Physico-chemical Descriptors log P, p, Rm, Vm, Pc and St - Figueroa-Valverde, Lauro; Díaz-Cedillo, Francisco; Garcia-Cervera, Elodia (Asian Journal of Chemistry, 2011)
In this work our initial design included the synthesis of montelukast-androsterone (5) and its relationship with several physico-chemical parameters as log P, p, Rm, Vm, PC and ST. The first step was achieved by the reacting between hemisuccinate of androsterone (1) with ethyleneadiamine to form an androsterone derivative (3) using N-(3-dimethylaminopropyl)-N'- ethylcarbodiimide or boric acid as catalysts. In the second stage, was achieved by reacting 3 with montelukast (4) to form 5 in presence of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide. Other results showed an increase in the values of log P, p, Rm, Vm, PC and ST in 5 with respect to 1, 3 and 4. These data suggest that physico-chemical parameters can affect the degree of lipophilicity of 5.